Globalization and Human Rights in the Developing World - Nault, Derrick M. author. aut Link
XII, 253 p.
Keywords: Focusing on world regions where human rights abuses are the most serious, extensive and sustained; this book fills a crucial gap in our knowledge of the difficulties and promise of promoting human rights in our global age.